Coexisting bilateral tracheal bronchi and accessory cardiac bronchus complicated with pneumonia and empyema: a case report - Behaylu Tesfamaryam; Belayneh Tsehay; Nadew Kemaw; Yisehak Abera (Journal of Medical Case Reports)
Abstract Background Tracheal bronchus and accessory cardiac bronchus are rare congenital anomalies of the tracheobronchial tree. Tracheal bronchus is a congenital anomaly in which the bronchus supplying all or part of the upper lobe originates from the trachea, carina, or another bronchus, while accessory cardiac bronchus arises from the medial wall of the bronchus intermedius. To our knowledge, this is the first reported case from Africa describing the simultaneous occurrence of bilateral tracheal bronchi and accessory cardiac bronchus. Case presentation A 45-year-old, non-smoking Ethiopian male of Halaba ethnicity presented with a chief complaint of a dry cough lasting 2 weeks. Chest examination revealed stony dullness and absent air entry over the right lower lung field. A non-contrast chest computed tomography scan showed right upper lobe pneumonia with empyema. Notably, the computed tomography scan also revealed bilateral tracheal bronchi supplying both the right and left upper lobes and an accessory cardiac bronchus. The patient was treated with broad-spectrum antibiotics and chest tube drainage for empyema and was discharged in an improved condition. Four months after discharge the patient returned to his pre-hospitalization activity level. Conclusion This case highlights the importance of recognizing these congenital anomalies, especially in patients with recurrent respiratory symptoms, to ensure appropriate diagnosis, prevention, and management of associated complications.